Sistem Informasi E-Raport dengan Metode User Centered Design (UCD) Berbasis Android - Khairi, Nadia Luthfiah; Nasution, Muhammad Irwan Padli (Jurnal Teknologi Sistem Informasi dan Aplikasi, 2024)
Madrasah Aliyah Miftahussalam is one of the schools whose address is Jalan Darussalam No.26 ABC, Sei Sikambing D, Medan Petisah, Sei Sikambing D, Kec. Medan Petisah, Medan City, North Sumatra 20119. The school has a website for report card distribution, but this website is not maintained regularly, so the website used for report card distribution cannot work properly. Not only that, using the website is also confusing for both the management and users of the website. The User Centered Design method can be used to solve this problem. This is because the UCD method develops an application based on user needs and can be developed based on Android. By using Android, report distribution will be easy. The Android application will be built using Android Studio, using the Firebase database with the Kotlin language. The UCD method refers to things that are really needed by users, the information needed regarding UAS, UTS and assignment scores can be managed and accessed easily. The implementation of Firebase and Kotlin language in building Android-based applications runs well and can be used easily.